1986
DOI: 10.1111/j.1469-8137.1986.tb00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Synthetase Isoforms in Algae

Abstract: SUMMARY The occurrence of glutamine synthetase isoforms in algae, from seven different phyla, has been investigated, using ion‐exchange chromatography. The algae have been classified into three groups according to their glutamine synthetase isoform content. The first group is characterized by having only the cytosolic glutamine synthetase, whereas the second group is distinguished by having only the chloroplastic glutamine synthetase. The third group is characterized by having both the isoenzymes. Stability st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
3
19
1
Order By: Relevance
“…The pH profiles for optimal activity of NADPH-GDH and both GS isoenzymes, GSl and GS2, indicate that these enzymes could function well in the pH environments of both the cell cytoplasm {c. pH 7) and the chloroplastic stroma {c. pH 8). In higher plants GSl is a cytoplasmic isoenzyme present in both chlorophyllous and non-chlorophyllous tissues, whereas GS2 is localized in the chloroplast (McNally et al, 1983;Casselton et al, 1986). Furthermore, NADPH-GDH in most green organisms is considered to be a chloroplastic enzyme (Stewart et al, 1980;Prunkard et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The pH profiles for optimal activity of NADPH-GDH and both GS isoenzymes, GSl and GS2, indicate that these enzymes could function well in the pH environments of both the cell cytoplasm {c. pH 7) and the chloroplastic stroma {c. pH 8). In higher plants GSl is a cytoplasmic isoenzyme present in both chlorophyllous and non-chlorophyllous tissues, whereas GS2 is localized in the chloroplast (McNally et al, 1983;Casselton et al, 1986). Furthermore, NADPH-GDH in most green organisms is considered to be a chloroplastic enzyme (Stewart et al, 1980;Prunkard et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…K, and V, , , values were determined using direct linear plots (Cornish-Bowden and Wharton, 1988 that it enables reliable and useful comparisons with other determinations such as rates of uptake, and this aspect may be particularly useful in studies involving metabolic control analyses (ap Rees and Hill, 1994). However, it should be noted that P. tricornutum possesses both the cytosolic and chloroplastic isoform of GS (Casselton et al, 1986), and, in Chlorella kessleri, the ratio of these two isoforms is different in nitrogen-replete and nitrogen-starved cells (Sumar et al, 1984). Comparisons of GS activities with maximum rates of ammonia uptake in P. tricornutum indicate that enzyme activities were close to the rates of uptake (Table 111).…”
Section: P Tricornutummentioning
confidence: 99%
“…The physiological significance of the existence of two isoenzymes of GS2 in leaves of higher plants (3,7,9,10,14) and in green algae (4,5,13) is not clear. Keys et al (8) have suggested that in higher plants the cytoplasmic isoenzyme (GS,) is responsible for reassimilation of photorespiratory ammonium, whereas primary ammonium assimilation is carried out by the chloroplast isoenzyme (GS,).…”
mentioning
confidence: 99%
“…Conflicting with this view are reports of a complete lack of GS, in many plants with high photorespiration rates (10). In green algae, where photorespiration usually appears to be low and not to involve rapid ammonium recycling (1 1, 12), the relative activities of the two isoenzymes vary considerably, and for several species, only GS, or GS2 is present (4). It has been suggested that an accurate evaluation of the relative activities of GS, and GS2 may not have been obtained in studies employing ion exchange media containing DTT and mercaptoethanol, which suppress GS, activity ( 1 5).…”
mentioning
confidence: 99%